2010
DOI: 10.1002/ange.200906610
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Structural and Chemical Stability of DNA in Hydrated Ionic Liquids

Abstract: Sicher aufbewahrt: Es wurde gezeigt, dass DNA in einer Vielzahl Cholin‐basierter hydratisierter ionischer Flüssigkeiten (ILs) löslich ist (siehe Bild). Die gelöste DNA ist außergewöhnlich langzeitstabil und liegt auch nach über einem Jahr unverändert vor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(18 citation statements)
references
References 26 publications
3
15
0
Order By: Relevance
“…24 The Journal of Physical Chemistry B Article stability is enhanced in the presence of IL, are in line with the earlier observations of enhanced thermal stability of DNA in choline and imidazole based ionic liquids. 7,19 The observation, i.e., an enhanced thermal stability of DNA in the presence of the IL, can be explained following the mechanism suggested by Auffinger and Jumbri. 19,44 According to them, the hydration shell around DNA is responsible for its thermal stability and with an increase in temperature an enhanced entropy of water molecules destabilizes the DNA.…”
Section: Fluorescence Correlation Spectroscopy Studymentioning
confidence: 87%
See 1 more Smart Citation
“…24 The Journal of Physical Chemistry B Article stability is enhanced in the presence of IL, are in line with the earlier observations of enhanced thermal stability of DNA in choline and imidazole based ionic liquids. 7,19 The observation, i.e., an enhanced thermal stability of DNA in the presence of the IL, can be explained following the mechanism suggested by Auffinger and Jumbri. 19,44 According to them, the hydration shell around DNA is responsible for its thermal stability and with an increase in temperature an enhanced entropy of water molecules destabilizes the DNA.…”
Section: Fluorescence Correlation Spectroscopy Studymentioning
confidence: 87%
“…14 Exceptional stability of DNA in the presence of choline based ILs is attributed to the slow rate of hydrolytic reactions in the presence of ILs. 7 Ding et al studied the interaction between [Bmim][Cl] and DNA using several analytical techniques and concluded that both electrostatic and hydrophobic interactions play important roles in the binding of IL to DNA. 15 Pang and co-workers estimated the binding parameters of [Bmim][BF 4 ] with DNA using an electrochemical micromethod.…”
Section: Introductionmentioning
confidence: 99%
“…6 Furthermore, through careful selection of cation−anion combinations, the chemical and physical properties of ILs can be modulated for task-specific applications. 7 Hence, this class of "designer" solvents continues to find increasing use in an expanding number of areas, including polymer chemistry as self-assembly media; 8 material chemistry for catalysis and synthesis; 9 biotechnology for biocatalysis, 10 biomolecular dissolution 11−13 and stability; 14,15 and electrochemistry for sensors, biosensors, and in electrochemical storage devices; 16 etc.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Likewise, DNA can be preserved for long-term usage under ambient conditions in hydrated ILs. 14 Similarly, the water content of hydrated ILs plays a crucial role in the dissolution and regeneration of cellulose from organic biomass. 17 The wide applications of IL/water binary mixtures have prompted many researchers to determine the thermophysical properties of this versatile solvent medium.…”
Section: ■ Introductionmentioning
confidence: 99%
“…13 They pointed out that high stability in the solvation structure arises from the hydrogen-bonding interactions of the cations and anions with the DNA bases as well as interactions between the cations and P-O bonds of phosphates in the DNA strands. On the other hand, strong interactions of the solvent ions with enzymes make them less stable and reduce their activity.…”
Section: Introductionmentioning
confidence: 99%